Impact of open distance learning professionalism & empowerment courses on clinical nurse practice - Rashidah Shahruddin; Saedah Muda; Siti Aishah Hashim Ali
Clinical nurse professionalism includes empowerment which is associated with increased nurse satisfaction and improved patient outcomes, both being elements of a healthy work environment. This study aims to compare the academic results of learners in open distance learning (ODL) professionalism course with the purported display of professional behaviour in clinical practice. In addition to demographic data, the survey included in quantifying information on nurses discerning qualities in displaying professionalism and empowerment in their daily nursing practice from their superiors and compared with the learner's academic results upon completion of the course. Data analysis using descriptive statistics involving 73 respondents (63%) from nurse supervisors who rated their nurses. Nurses moral principle is rated highest on acting honestly (65.8%), followed by acting justly (58.9%). On personal integrity, nurses can look after their own wellbeing (56.2%) and act under pressure (58.9%). Their expertise skills showed ability in working and acting independently and being autonomous (50.7%). Their power of making decisions is 52.1% in the clinical area. Nurses who are future-oriented can promote new ideas at the workplace (52.1%), and their sociability level is 50.7% in solving problems responsibly. The above professionalism and empowerment qualities showed a positive trend and relevancy with their academic performance. In conclusion, this study professed to show academic performance of nurses from the course is internalised and visible in their professional behaviour in the clinical area.